Motivation, Supervisor Support and Training Effectiveness at Universiti Utara Malaysia - Mariatul Atiqah, Mohd Akhir (2010)
The main purpose of this study is to determine the relation between motivation, supervisor support and training effectiveness among employee in academic institution. Data were collected from 97 employees by using simple random sampling and the sample taken from Bursars Department, Academic Affair Department, Registrar's Department and Library Department in Universiti Utara Malaysia. A questionnaire consisting 21 questions was administrative to the respondents. The study showed that the employees do display that the motivation and supervisor support has relationship with training effectiveness.